Design recommendations for harm reduction in drug usage: a redesign study of Bia with a user-centered approach - Juy, Carmen Li (2022)
mHealth technologies emerged with the potential to revolutionize the way people have access to health- related services and information and have commonly been developed to provide health education and support behav- ior change. However, many of these applications deliver a negative user experience (UX) as they lack components such as desirable functionalities, interface quality, or usage context adequacy, resulting in a gap in user retention. One mHealth sub-domain that is still not widely explored is the consumption of illicit and licit psychoactive sub- stances, especially related to harm reduction practices. This study presents the redesign process of Bia, a mHealth application directed to promote harm reduction practices on drug usage in Brazil. The goal of the redesign was to address the usability and content issues identified by a multidisciplinary evaluation and refine the overall prod- uct to enhance the probability of delivering a positive experience for the end-users. For that goal, we employed a user-centered design (UCD) approach that encompassed user research, conceptualization workshops with different stakeholders, and two cycles of prototype design and user evaluation. All steps of the redesign were conducted online. The results show how the outputs of each step contributed to developing Bia 2.0, which the final design was analyzed in a preliminary UX evaluation using the User Experience Questionnaire (UEQ) and presented an excellent level of UX. We also highlight our main challenges and delineate some design recommendations based on this redesign case and standardized design recommendations.